Cerebrovascular diseases in the elderly: the challenge of multiple aneurysms. (3rd August 2014) - Crobeddu, Emanuela; Panciani, Pier Paolo; Garbossa, Diego; Pilloni, Giulia; Fornaro, Riccardo; Ronchetti, Gabriele; Spena, Giannantonio; Tartara, Fulvio; Ducati, Alessandro; Fontanella, Marco
Abstract : Objective : The worldwide population aging and the nowadays medical advances impose to consider new management guidelines for elderly. Aim of this study was to assess the best treatment in elderly with multiple intracranial aneurysms (MIA). Methods : From 1994 to 2011, we admitted 1462 patients with ruptured cerebral aneurysm. Among those aged ≥65 years, 43 had MIA (15% of elderly). Size and aneurysm location, timing and type of treatment were analyzed. Patients were thus stratified according to Hunt-Hess grade on admission and evaluated at 6 months using the Glasgow Outcome Scale (GOS). Results : We had 87 aneurysms in the final series. Three patients died because of the impossibility to treat the ruptured aneurysm. No new bleeding from untreated aneurysms was observed; no retreatment after previous coiling was performed. Conclusions : MIA lead to significantly poorer outcomes, especially in elderly, because of their general clinical condition, presence of risk factors and lower capacity of reaction to stressful events. In patients without large hematomas, coiling of the ruptured aneurysm represents the procedure with high effectiveness. The clinical conditions on admission represent the most important factor for the treatment results. To reduce the treatment-related risks we do recommend a conservative approach for the unruptured aneurysms.